SISTEM MANAJEMEN TEKNISI IT HELPDESK DI RUMAH SAKIT HASYIM ASY’ARI BERBASIS WEBSITE - Milaniyah R.J, Aisyah; Kristianto , Hery (Inovate, 2025)
Quick response to complaints about information technology problems is very important in supporting the stability of hospital operations. The aim of this internship activity is to develop a Technician module for the web-based IT Helpdesk system at Hasyim Asy'ari Jombang Hospital. Requirements analysis is part of system development to ensure that features are available, allowing technicians to receive complaint reports, manage repair tasks, and update problem resolution status. For system development, the CodeIgniter Framework was used, and the testing focused on workflow efficiency and ease of use for technicians. Implementation results show that the Technician module in the IT Helpdesk increases response and problem resolution by up to 25%, reduces system downtime, and speeds up operational recovery of IT services. This system provides a solution that supports technicians in carrying out their duties effectively and increases the stability of IT operations in hospitals. Keywords: IT Helpdesk Technician, IT complaints, hospital, IT monitoring, CodeIgniter.